TikTok as a constructivist platform for ethically and algorithmically literate TESL in the industrial era 5.0 - Ninik Suryatiningsih; Dwi Priyo Utomo; Joko Widodo; Masduki Masduki (Institute of Advanced Engineering and Science, 2026)
This research places the integration of TikTok in teaching English as a second language (TESL) as a directed pedagogic design that combines constructivist engagement, digital ethics, and algorithmic literacy in the context of the industrial era 5.0. This study aims to: i) examine the influence of constructivist engagement on speaking fluency; ii) assess the effectiveness of digital ethics rubrics; and iii) test the mediating role of algorithmic literacy. Using a sequential mixed method, the study involved 130 participants (120 students, 10 lecturers) in a 12-week intervention that included ethics orientation and algorithmic literacy, task modeling, micro-speaking video production, rubric-based peer-lecturer feedback, and reflection and revision. Quantitative data were analyzed by regression, paired t-test, analysis of variance (ANOVA), and mediation analysis, while qualitative data were analyzed thematically and integrated through joint displays. Results showed that constructivist involvement had a significant effect on speaking fluency (β=0.68; R²=0.46; p